A micromechanical investigation of soil-structure interface behaviour - Pettey, Angus (2023)
A limiting factor in the drive to deliver performance-based design is the lack of knowledge regarding the constitutive behaviour of soil-structure interfaces, particularly in the case of cyclic loading. Attempts to model the behaviour of these interfaces have failed to consider the long-term effects of cyclic loading, in particular how both the soil and structure may degrade over the course of thousands of cycles. To address this shortfall in understanding, consideration must be given to not only the geotechnical aspects of the interface, but also the structural aspects, and how these two components interact over the course of a structure's lifetime. This thesis presents a micromechanical investigation of the behaviour of soil-structure interfaces, with a particular focus on these cyclic effects by carrying out novel experimental testing at the macro-scale and single-particle scale.